Development of a Smart Box based on discovery learning to increase the learning interest of elementary school students - Silviana Nur Faizah; Yunita Nur Maulidiyah (Journal of Integrated Elementary Education, 2026)
This study aims to develop Smart Box media for Natural and Social Sciences learning using the ADDIE model. A needs analysis revealed that students struggled with abstract concepts and required interactive media to enhance understanding. The Smart Box was designed as an interactive multimedia tool combining visuals, audio, and manipulative activities to support active learning. Validation by experts in media, material, and language showed high validity scores: media (88.33%), material (89.58%), and language (92.5%). These scores assess aspects of design, feasibility, accuracy, relevance, readability, and clarity. Field trials involving students yielded a very positive response with a score of 96%, evaluating comprehension, attractiveness, ease of use, and usefulness. The results indicate that the Smart Box media is feasible, engaging, and effective in improving student motivation, conceptual understanding, and active participation in social studies learning. This study suggests that Smart Box media has strong potential as an innovative learning tool, specifically for natural and social sciences in elementary education.